2018
DOI: 10.1002/gps.4863
|View full text |Cite
|
Sign up to set email alerts
|

Can you detect early dementia from an email? A proof of principle study of daily computer use to detect cognitive and functional decline

Abstract: ObjectiveTo determine whether multiple computer use behaviours can distinguish between cognitively healthy older adults and those in the early stages of cognitive decline, and to investigate whether these behaviours are associated with cognitive and functional ability.MethodsOlder adults with cognitive impairment (n = 20) and healthy controls (n = 24) completed assessments of cognitive and functional abilities and a series of semi‐directed computer tasks. Computer use behaviours were captured passively using b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Older people (over the age of 65 years) with SCD, MCI, and mild dementia due to AD were recruited for steps 1 and 3 through memory clinics; the UK dementia research registry "Join Dementia Research" (a national web-based service for participation in dementia studies); step 3 participants were also part of another study called Software Architecture for Mental Health Self-Management (SAMS) (Stringer et al, 2018). Participants with dementia and MCI diagnoses were referred with a diagnosis already made by qualified memory specialists.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Older people (over the age of 65 years) with SCD, MCI, and mild dementia due to AD were recruited for steps 1 and 3 through memory clinics; the UK dementia research registry "Join Dementia Research" (a national web-based service for participation in dementia studies); step 3 participants were also part of another study called Software Architecture for Mental Health Self-Management (SAMS) (Stringer et al, 2018). Participants with dementia and MCI diagnoses were referred with a diagnosis already made by qualified memory specialists.…”
Section: Participantsmentioning
confidence: 99%
“…Participants with self-reported worries about their memory were identified as SCD if they indicated on a scale of functional capacitythe Everyday Cognition Scale (ECog) (Farias et al, 2008) that they were "concerned they have a memory or other thinking problem" and their total score on this scale was >1.436. This cutoff score corresponds to the upper 95% confidence interval of the mean total ECog scores from a sample of healthy control participants who indicated that they were not "concerned they have a memory or other thinking problem" (Stringer et al, 2018). Participants who did not meet this criterion for SCD were not eligible to take part.…”
Section: Participantsmentioning
confidence: 99%
“…Significant resources are being invested in developing new assistive and diagnostic technologies for the elderly or those living with dementia (e.g. [10], [11]) as increasing life expectancy leads to increases in the incidence of dementia. The potential health-related benefits offered by technology are counterweighted by societal, legal and ethical challenges [14] and many governments are seeking to define forwardlooking policies on dementia care (e.g.…”
Section: The 'What If?' Case Studymentioning
confidence: 99%
“…Other modalities aside from voice has also been investigated and found to be good predictors for cognitive decline and dementia including eye movement Parsons et al (2017); Zhang et al (2016), olfactory Karunanayaka et al (2017); Lafaille-Magnan et al (2015) and even hand dexterity Stringer et al (2018).…”
Section: Introductionmentioning
confidence: 99%